A produção da habitação social numa cidade amazônica - José Aldemir de Oliveira; Crizan Graça de Souza (Confins)
This paper discusses the housing derived from public policies in cities located in the Brazilian Amazon and how these policies affects the lifehoods of local residents. It is shown that the geography of the cities that receive these projects becomes more complex. Interests of various agents producing the space seek to guarantee the extended reproduction of capitalist relations in the most distant places of the Amazon, especially in riverside cities. The results presented are based on extensive fieldwork done in Parintins, Amazonas state, during the years 2016 and 2017. The aim of the fieldwork was to identify the differences and similarities of the production of social housing in the city of Parintins comparing the first groups of housing projects financed by National Housing Bank (Banco Nacional de Habitação – BNH) and the most recent ones by Federal Cashier (Caixa Econômica Federal - CEF) through the My House My Life Program (Programa Minha Casa Minha Vida - PMCMV). The results have shown that the production of social housing implies in changes in space, such as the expansion of the city, the insertion of the housings into the urban structure, the rise in number of enterprises and urban equipments built. These results appear implicitly in questions that are difficult to quantify due to the fact that they go beyond the architectural forms and are related to the dimensions of the lifehoods.